The efficiency of ProTaper rotary retreatment files in the removal of two different root filling materials (Mustansiria Dental Journal, 2018)
The ProTaper rotary retreatment files is one of the new files especially designedfor retreatment. The aim of this study is to test if root canals filled with Resilon pointsand RealSeal sealer (SybronEndo, USA) can be retreated using ProTaper rotaryretreatment files in the same manner as canals filled with gutta-percha and zinc oxideeugenol based sealer.Twenty extracted maxillary first molars with palatal roots having single straightcanal and fully formed apex were instrumented and randomly divided into two groupsof ten roots each according to the root filling material used (gutta-percha and zincoxide eugenol based sealer for group A and Resilon points and RealSeal sealer forgroup B). For all roots, removal of root filling material was done by using ProTaperrotary retreatment files (Dentsply-Maillefer, Ballaigues, Switzerland). The amount ofroot filling material remained and the time required for the removal process for allroots were recorded and statistically analyzed using SPSS version 15.The results showed that during retreatment procedures; removal of Resilon withRealSeal sealer from root canals can be achieved with ProTaper rotary retreatmentfiles but the amount of Resilon root filling material remained was more than GP andshowed a highly significant difference, it was also obvious that removal of Resilonroot filling material from root canals requires more time than roots filled with guttapercha.In conclusion, removal of resin based root filling material can be achieved withProTaper rotary retreatment files but it leaves more filling remnants and takes moretime than canals filled with gutta-percha.